2022
DOI: 10.1093/mnras/stac1207
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Lyman-α emission line: towards the understanding of galactic properties extracted from Lyα spectra via radiative transfer modelling

Abstract: Existing ubiquitously in the Universe with the highest luminosity, the Lyman-α (Lyα) emission line encodes abundant physical information about the gaseous medium it interacts with. Nevertheless, the resonant nature of the Lyα line complicates the radiative transfer (RT) modeling of the line profile. We revisit the problem of deciphering the Lyα emission line with RT modeling. We reveal intrinsic parameter degeneracies in the widely-used shell model in the optically thick regime for both static and outflowing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 63 publications
2
10
0
Order By: Relevance
“…Previous modeling work found that the velocities of expanding (outflowing) or collapsing (accreting) shells are well-constrained for emission lines with distinct, asymmetric double peaks (Li & Gronke 2022). Figure 6 compares the observed Lyα flux ratios to the H I velocities derived from the shell models in this work that do and do not account for resonant scattering.…”
Section: Model H I Velocities Probe Kinematics Of Accretion and Outflowsmentioning
confidence: 73%
See 3 more Smart Citations
“…Previous modeling work found that the velocities of expanding (outflowing) or collapsing (accreting) shells are well-constrained for emission lines with distinct, asymmetric double peaks (Li & Gronke 2022). Figure 6 compares the observed Lyα flux ratios to the H I velocities derived from the shell models in this work that do and do not account for resonant scattering.…”
Section: Model H I Velocities Probe Kinematics Of Accretion and Outflowsmentioning
confidence: 73%
“…However, it is clear that a real scattering geometry is neither isotropic nor does it have constant velocity and density profiles as assumed in the shell model. There is, therefore, an ongoing debate in the literature regarding the usefulness of shell model fitting as well as the physical interpretation of the derived parameters (e.g., Orlitova et al 2018;Li & Gronke 2022). What is clear from this debate is that shell model parameters cannot be interpreted literally, if at all, but instead represent some weighted quantity probed by Lyα photons.…”
Section: Resonant Scattering In a Spherical Shellmentioning
confidence: 99%
See 2 more Smart Citations
“…Orlitová et al 2018), the intrinsic width of Ly𝛼 recovered by the radiative transfer models results to be significantly larger than the one of the Balmer lines (for our target a factor ∼ 3.4 larger if compared to our estimate of the H𝛽 line, in line with the results from Orlitová et al 2018). According to Li & Gronke (2022), however, this discrepancy is most likely due to additional radiative transfer effects and, in particular, the possibility that the Ly𝛼 propagates within a clumpy gas distribution with velocity dispersions 100 km/s. Since 'shell-models' are an oversemplification of the complex structure and kinematics of Ly𝛼-emitters and their surroundings, it is currently debated how much of the radiative transfer is indeed captured by the models and the real meaning and reliability of the involved parameters, especially T and 𝜏 𝑑 .…”
Section: Spectral Properties Of the Ly𝛼mentioning
confidence: 99%